85.9k views
3 votes
What is the solution of the system? Use elimination.
5x + 6y = 17
−10x − 9y = −43

User Radoslav
by
5.4k points

1 Answer

1 vote

By using elimination method the solution for the given equations 5x+6y=17 and -10x-9y= -43 are x=7 and y= -3.

Explanation:

The given equations are,


5x+6y=17..................................(1)


-10x-9y=-43..............................(2)

Step:1

By elimination method,

Multiplying the equation (1) by 9 ( Eqn (1) × 9)


45x+54y=153.................................(3)

Multiplying the equation (2) by -6 ( Eqn (2) × -6)


60x+54y=258................................(4)

Step:2

Subtracting the Equations (3) and (4),


45x+54y=153


60x+54y=258

( - )

(
45x-60x ) + (
54y-54y ) = (
153-258 )

(
-15x ) = (
-105 )


x = 7

Step:3

Substitute the x=7 in equation (1),


5x+6y=17

( 5 × 7 ) + (
6y ) = 17


6y = -18


y = -3

Step:4

Check for solution,

Substitute the x and y values in Eqn (1),


5x+6y=17

( 5 × 7 ) + ( 6 × -3 ) = 17

( 35 ) - ( 18 ) = 17

17 = 17

Result:

The solution for the equations 5x+6y=17 and -10x-9y= -43 are x=7 and y= -3.

User Yusuf Ibrahim
by
5.5k points